Formulasi Tablet Hisap Ekstrak Etanol Daun Kemangi (Ocimum Sanctum L.) dengan Natrium Karboksimetilselulosa Sebagai Bahan Pengikat Terhadap Sifat Fisik Tablet: Formulation Of Basil Leaf (Ocimum Sanctum L.) Ethanol Extract with Carboxymethyl Cellulose as A Binding Material: Physical Properties of Tablets - Muhammad Ihsan Karimka; Anita Dwi Septiarini; Bangkit Riska Permata (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2023)
So far, the basil plant (Ocimum sanctum L.) has been used by the community as a fresh vegetable to overcome the problem of bad breath. Ethanol extract in basil can inhibit the growth of pathogenic bacteria in the mouth. This study aims to make lozenges of basil extract with different concentrations of CMC-Na as a binder and to determine the effect of CMC-Na concentrations on the physical properties of lozenges. Lozenges were made by the wet granulation method with 0% CMC-Na binder variation for formula I; 1% for formula II; 3% for formula III; 5% for formula IV; 7% for formula V. Granules are compressed using a single punch tablet machine. The results showed that the use of CMC-Na as a binder in the manufacture of lozenges of basil extract in all formulas produced lozenges that met the requirements, except for formulas I and II. The best hardness test results were in formula V, with a value of 5.28 kg/cm2, while the best friability test was in formula IV, with a value of 0.32%. The best dissolving time test results were in formula V with a dissolving time of 6 minutes 33 seconds. The results of the taste response test showed that formula V had the most delicious taste response. The effect of binder concentration can affect the physical properties of the tablet. Variations in the binder influence each formula. The greater the binder, the greater the level of hardness increases.